2010
DOI: 10.1097/tp.0b013e3181f5c3bf
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Term Outcomes Associated With Kidney Transplantation in Recipients 80 Years and Older: An Analysis of the OPTN/UNOS Database

Abstract: Although perioperative mortality was uncommon among elderly recipients (1.5%), a trend toward higher perioperative mortality was observed in recipients 80 years and older. There was no difference in survival among standard criteria donor and ECD recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 12 publications
4
48
1
6
Order By: Relevance
“…The authors observed no difference in the rate of acute rejection during the initial hospitalization or at 1 year [19]. In the analysis, 73% of transplant recipients in the 80 years and older group were alive at 2 years [19] exceeding the expectation of the 2-year survival rate of 44% for a dialysis patient aged 80 to 84 years according to the USRDS database [15]. The overall perioperative mortality risk at 30 days was low at 1.5% for the overall cohort of elderly patients with a trend towards a higher perioperative mortality rate at 2.5% for the aged 80 years and older cohort [19].…”
Section: Nephrology Consultationmentioning
confidence: 82%
See 3 more Smart Citations
“…The authors observed no difference in the rate of acute rejection during the initial hospitalization or at 1 year [19]. In the analysis, 73% of transplant recipients in the 80 years and older group were alive at 2 years [19] exceeding the expectation of the 2-year survival rate of 44% for a dialysis patient aged 80 to 84 years according to the USRDS database [15]. The overall perioperative mortality risk at 30 days was low at 1.5% for the overall cohort of elderly patients with a trend towards a higher perioperative mortality rate at 2.5% for the aged 80 years and older cohort [19].…”
Section: Nephrology Consultationmentioning
confidence: 82%
“…The authors observed no difference in the rate of acute rejection during the initial hospitalization or at 1 year [19]. In the analysis, 73% of transplant recipients in the 80 years and older group were alive at 2 years [19] exceeding the expectation of the 2-year survival rate of 44% for a dialysis patient aged 80 to 84 years according to the USRDS database [15].…”
Section: Nephrology Consultationmentioning
confidence: 99%
See 2 more Smart Citations
“…Kidney transplantation offers the potential for improved quality and length of life for elderly patients (2-4), and reasonable outcomes have been reported for selected patients in their 70s and even 80s (3,4). However, the proportion of elderly patients on the transplant waiting list and receiving subsequent transplants remains relatively small: Approximately 9% of prevalent ESRD patients 60 or older were on the transplant waiting list in 2008.…”
mentioning
confidence: 99%